Olá, Weverton. Podem considerar encerrado o andamento deste artigo no Serviço de Editoração Científica (SEC) da Biblioteca Central da UFG. Atenciosamente, Thiago - Alessandra Fernandez da Silva; Alana Pinto De Melo; Anita Marchionatti Pigatto; Rafaella Silva Rocha; Maiara Poersch Seibel; Natália Pons Méndez; João Antonio Tadeu Pigatto (Ciência Animal Brasileira)
This study was conducted to evaluate the viability of porcine corneal endothelium after conditioning in the preservation medium Eusol-C. Twelve eyes from six 6-month-old male Large White pigs (Sus scrofa domesticus) were analyzed. Endothelial cell morphology and cell count of all samples were assessed prior storage using specular microscopy to ensure that only healthy corneas were included in the study. The samples were randomly divided into a control group (G1) and a test group (G2). Corneas from G1 were immediately submerged in bottles containing 2.5% glutaraldehyde, whereas corneas from G2 were stored in Eusol-C at 4°C for 14 days. The percentage of endothelial cell loss was evaluated using scanning electron microscopy (SEM). Comparisons between regions were performed using repeated measures Analysis of Variance (ANOVA). Differences were considered statistically significant at P < 0.05. Corneal samples from G1 showed no areas of endothelial cell loss. In samples from G2, the average cell loss was 3.01%. In conclusion, the hypothermic medium Eusol-C satisfactorily preserved porcine corneas for up to 14 days.